2005
DOI: 10.1016/j.socscimed.2004.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Non-antibiotic treatment recommendations: delivery formats and implications for parent resistance

Abstract: This study draws on a database of 570 community-based acute pediatric encounters in the USA and uses conversation analysis as a methodology to identify two formats physicians use to recommend non-antibiotic treatment in acute pediatric care (using a subset of 309 cases): recommendations for particular treatment (e.g., ''I'm gonna give her some cough medicine.'') and recommendations against particular treatment (e.g., ''She doesn't need any antibiotics.''). The findings are that the presentation of a specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 42 publications
3
150
0
5
Order By: Relevance
“…Third, the reason that I undertake such an analysis is because of my interest in the way in which the mechanics of conversation were implicated in the development of understanding that culminated in a decision. Though this resonates with recent research on talk in institutional settings where decisions are sometimes involved (Clayman and Reisner 1998;Stivers 2005; see also Maynard, Freese, and Schaeffer 2010), I am much more interested in how talk was used to construct a "mental model"-or rather, its discursive equivalent-of the alternatives and their consequences, on the basis of which a difficult decision could be justifiably made.…”
Section: Methodsmentioning
confidence: 59%
“…Third, the reason that I undertake such an analysis is because of my interest in the way in which the mechanics of conversation were implicated in the development of understanding that culminated in a decision. Though this resonates with recent research on talk in institutional settings where decisions are sometimes involved (Clayman and Reisner 1998;Stivers 2005; see also Maynard, Freese, and Schaeffer 2010), I am much more interested in how talk was used to construct a "mental model"-or rather, its discursive equivalent-of the alternatives and their consequences, on the basis of which a difficult decision could be justifiably made.…”
Section: Methodsmentioning
confidence: 59%
“…Hence the ''patient pressure'' theory is not entirely credible, except as a partial explanation. It has been shown that the presentation of a specific affirmative recommendation for treatment is less likely to engender parent resistance to a nonantibiotic treatment recommendation than a recommendation against a particular treatment even if the doctor later offers a recommendation for a particular treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, clinical disciplines have struggled with implementing client-centered models of decision making. Providers must reconcile potential conflicts among clinical evidence, local practice, and client-centered care (Burkell & McKenzie, 2005;Levy, 1999), especially in situations where a client's choice conflicts with the clinician's own preferences (Delany, 2007;Lehtinen & Kääriäinen, 2005), or with population benefits (Raffle, 2001;Seavilleklein, 2009;Hargreaves, Stewart, & Oliver, 2005) or acceptable clinical practice (e.g., Stivers, 2005;Whitney et al, 2008). Midwives may need to negotiate several competing interests (Burkell & McKenzie, 2005), and Levy (1999) found that they controlled the release of information in order to protect women and themselves.…”
Section: Discussionmentioning
confidence: 99%